Afritoxinones A and B, dihydrofuropyran-2-ones produced by Diplodia africana the causal agent of branch dieback on Juniperus phoenicea - Evidente, Antonio; Masi, Marco; Linaldeddu, Benedetto T.; Franceschini, Antonio; Scanu, Bruno; Cimmino, Alessio; Andolfi, Anna; Motta, Andrea; Maddau, Lucia (PHYTOCHEMISTRY, 2012)
Two phytotoxic dihydrofuropyran-2-ones, named afritoxinones A and B. were isolated from liquid culture of Diplodia africana. a fungal pathogen responsible for branch dieback of Phoenicean juniper in Italy. Additionally, six others known metabolites were isolated and characterized: oxysporone, sphaeropsidin A, epi-sphaeropsidone, R-(-)-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-4-hydroxymellein. The structures of afritoxinones A and B were established by spectroscopic and optical methods and determined to be as (3aS{*},6R{*}-,7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-o ne and (3aR{*},6R{*},7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-on e, respectively. The phytotoxic activity of afritoxinones A and B and oxysporone was evaluated on host (Phoenicean juniper) and non-host plant (holm oak, cork oak and tomato) by cutting and leaf puncture assay. Oxysporone proved to be the most phytotoxic compound. This study represents the first report of secondary metabolites produced by D. africana. In addition, the taxonomic implications of secondary metabolites in Botryosphaeriaceae family studies are discussed. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Afritoxinones A and B; Botryosphaeriaceae; Diplodia africana; Juniperus phoenicea; Phytotoxins

Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Sphaeropsidones, Phytotoxic Dimedone Methyl Ethers Produced by Diplodia cupressi: A Structure−Activity Relationship Study - Evidente, Antonio; Maddau, Lucia; Scanu, Bruno; Andolfi, Anna; Masi, Marco; Motta, Andrea; Tuzi, Angela (Journal of Natural Products, 2011)
Sphaeropsidone and episphaeropsidone are two phytotoxic dimedone methyl ethers produced by Diplodia cupressi, the causal agent of a canker disease of cypress in the Mediterranean area. In this study, eight derivatives obtained by chemical modifications and two natural analogues were assayed for phytotoxic and antifungal activities, and a structure?activity relationship was examined. Each compound was tested on nonhost plants and on five fungal pathogenic species belonging to the genus Phytophthora. The results provide insights into structure?activity relationships within these compounds. It was found that the hydroxy group at C-5, the absolute C-5 configuration, the epoxy group, and the C-2 carbonyl group appear to be structural features important in conferring biological activity. The conversion of sphaeropsidone into the corresponding 1,4-dione derivative led to a compound showing greater antifungal activity than its precursor. This finding could be useful in devising new natural fungicides for practical application in agriculture.
doi: 10.1021/np100837rdoi: 10.1021/np100837rThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: antifungal activity (voyant); Diplodia cupressi; Phytotoxicity; Sphaeropsidones

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393l

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela; Maddau, Lucia; Franceschini, Antonio; Marras, Francesco; Motta, Andrea (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393ldoi: 10.1021/np050393lThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Chemical characterization; Diplobifuranylones; Diplodia corticola; metabolites; Phytotoxicity (voyant)

Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 12608876
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships